2007
DOI: 10.1107/s0907444907016204
|View full text |Cite
|
Sign up to set email alerts
|

Structural and pharmacological comparison of daboiatoxin fromDaboia russelli siamensiswith viperotoxin F and vipoxin from other vipers

Abstract: Russell's viper (Vipera russelli, also known as Daboia russelli) is one of the major causes of fatal snakebites. To date, five Daboia russelli subspecies have been recognized. Daboiatoxin (DbTx) is the main lethal phospholipase A(2) (PLA(2)) toxin in the venom of D. russelli siamensis (Myanmar viper) and has strong neurotoxic, myotoxic and cytotoxic activities. DbTx and its homologous neurotoxins viperotoxin F from D. russelli formosensis (Taiwan viper) and vipoxin from the Bulgarian sand viper V. ammodytes me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Fourteen conserved cysteines of sPLA 2 form seven disulfide bridges that stabilize the tertiary structure. These proteins share a homologous core and invariant tertiary structure [27,28] that in- Fig. (1).…”
Section: Structure Of Phospholipases a 2 S (Pla 2 S)mentioning
confidence: 99%
“…Fourteen conserved cysteines of sPLA 2 form seven disulfide bridges that stabilize the tertiary structure. These proteins share a homologous core and invariant tertiary structure [27,28] that in- Fig. (1).…”
Section: Structure Of Phospholipases a 2 S (Pla 2 S)mentioning
confidence: 99%
“…While envenoming by Chinese D. siamensis has not been reported to produce clinically evident neurotoxicity, we have shown the venom displays pre-synaptic neurotoxicity and myotoxicity in the chick biventer cervicis nerve-muscle preparation [ 34 ]. These activities of the venoms from Daboia species have been attributed to the presence of PLA 2 s, both clinically and in vitro [ 13 , 15 , 18 , 32 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…These effects are likely to be attributable to the PLA 2 component(s) of the venom. PLA 2 activity in Daboia species venoms has previously been reported [ 7 , 10 , 12 , 14 ], and Tan et al [ 16 ] confirmed the presence of putative PLA 2 toxins in Guangxi D. siamensis venom. However, it is uncertain whether the PLA 2 toxins of D. siamensis venom are responsible for in vitro myotoxic effects.…”
Section: Discussionmentioning
confidence: 71%
“…However, other clinical outcomes, including local swelling, blistering ecchymosis, hypopituitarism, generalised capillary permeability, neurotoxicity, and myotoxicity, are geographically disjunct [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Comparative proteomic studies elucidated the diverse composition of Daboia species venoms from different regions of South-East Asia, supporting the variable clinical effects observed following snake envenomation from different locations [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation